Neoadjuvant Immune Checkpoint Inhibitors Plus Chemotherapy in Locally Advanced Esophageal Squamous Cell Carcinoma: Perioperative and Survival Outcomes - Ma, Xiao; Zhao, Weixin; Li, Bin; Yu, Yongfu; Ma, Yuan; Thomas, Mathew; Zhang, Yawei; Xiang, Jiaqing; Zhang, Yiliang (Frontiers in Oncology, 2022)
Abstract Background: Immune checkpoint inhibitors (ICI) improve survival in patients with late-stage esophageal squamous cell carcinoma (ESCC) but have not been fully evaluated in locally advanced ESCC. Method: We retrospectively assessed outcomes of consecutive, treatment-naïve locally advanced ESCC (stage III or IVA) adults treated with neoadjuvant ICI plus chemotherapy followed by surgery, who refused or lacked access to radiotherapy, with regards to surgery feasibility, pathological response, and relapse-free survival (RFS). Results: We uneventfully treated 34 patients with the combined regimen in 2020. None reported grade III or higher toxic effects. All underwent surgery as planned: 32 received complete (R0) resections and 2 had microscopically positive margins (R1). Tumor downstaging occurred in 33 (97.1%) patients and 11 (32.4%) had pathologically complete response of the primary lesion. Median postoperative length of stay was 12 days (interquartile range: 11 to 17). All patients resumed a semi-liquid diet on discharge. The 90-day postoperative morbidity rate was 20.6% (7/34) with no mortalities. The 1-year RFS was 77.8% [95% CI, 64.2-94.2]. Conclusion: Neoadjuvant ICI plus chemotherapy was safe and resulted in significant downstaging, rendering inoperable tumors operable, relieving symptoms of dysphagia and prolonging survival for locally advanced ESCC patients who refused or lacked access to radiotherapy.